Natural Resources Endowment and African' Countries Private Enterprises Productivity - Akouwerabou, B. Denis; Adbi, Yuya A.; Legala Keudem, G. G. (Archives of Business Research, 2018)
Abundant literature has focused on the phenomenon called "the curse of natural resources". So far, all authors who have studied the resource curse have focused on the relationship between the endowment of natural resources and macroeconomic growth. We empirically test the existence of this phenomenon using the data of 6581 private enterprises from twenty-four African countries that are rich and poor in natural resources. The data show that enterprises that are set up in countries extracting huge quantities of energizing natural resources are inefficient compared to those in countries poor in natural resources. The extent of the harmful effect of the richness in natural resources on enterprises’ productivity is still more important in countries where share of natural resources in exportation income is very high.